2010
DOI: 10.1007/s12160-010-9174-8
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke Policy and the Risk of Depression

Abstract: Background Banning smoking in work and public settings leads to immediate reductions in disease burden. However, no previous studies have looked specifically at the impact smoking bans may have on depression. Methods The 2006 Behavioral Risk Factor Surveillance System (BRFSS) uses a cross-sectional design representative of the non-institutionalized civilian US population. Never smoker survey participants ≥18 years of age were selected from the BRFSS (n=41,904) with their self-report of depressive symptoms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
(30 reference statements)
3
11
0
Order By: Relevance
“…FA + dLAN exposed mice also had less of a preference for sucrose-water compared to FA + LD exposed mice. These results correlate with previous literature 14,21,28,33-35 and suggest exposure to PM 2.5 and dLAN cause depressive-like behaviors in rodents and regulate mood.…”
Section: Discussionsupporting
confidence: 92%
“…FA + dLAN exposed mice also had less of a preference for sucrose-water compared to FA + LD exposed mice. These results correlate with previous literature 14,21,28,33-35 and suggest exposure to PM 2.5 and dLAN cause depressive-like behaviors in rodents and regulate mood.…”
Section: Discussionsupporting
confidence: 92%
“…None of the previous studies evaluated the effect of SHS exposure in public places, so we were unable to compare this result with others. The recently published study of US population also reported that there was no statistically significant association between smoking policies in public work areas and major depression (Bandiera et al, 2010b). Our results provided more detailed epidemiological evidence to suggest that SHS exposure in homes or in workplaces were associated with increased odds of depressive symptoms.…”
Section: Discussionsupporting
confidence: 59%
“…Studies have shown that banning smoking in work and public settings leads to immediate reductions in disease-specific symptoms and disease burden (Bartecchi et al, 2006;Ferrante et al, 2012), and participants living where smoking was allowed anywhere in the home or in work areas had more depressive symptoms compared with those reporting complete smoking bans (Bandiera et al, 2010b). In addition, these data suggest that interventions designed to eliminate smoking in the home are also needed.…”
Section: Discussionmentioning
confidence: 96%
“…40,41 There is also a growing body of literature implicating second hand smoke exposure to depressive symptoms. 42,43 Furthermore, exposure to air pollution is directly associated with emergency department visits for suicide attempts. 44 One limitation of this study is that the effects of PM exposure were only evaluated in male mice.…”
Section: Discussionmentioning
confidence: 99%